Preterm infant cues during breastfeeding and its measurement: A scoping review - Haryatiningsih Purwandari; Meivita Dewi Purnamasari; Wastu Adi Mulyono; Mei-Chih Huang (Belitung Nursing Journal, 2023)
Background: Preterm infants display certain behaviors to communicate their needs, known as preterm infant cues. However, the existing research on preterm infant cues primarily draws from studies conducted on bottle-fed infants rather than breastfed infants. Objective: This study aimed to investigate the concept of preterm infant cues during breastfeeding and its appropriate instruments. Design: A scoping review. Data Sources: The articles published up to January 2022 were searched from multiple sources from EBSCOhost Web, namely CINAHL Plus with Full Text, MEDLINE, ERIC, and E-Journals. Review Methods: The articles retrieved for this review were screened using PICO (Population, Intervention, Comparison, and Outcomes) format.Preferred Reporting Items for Systematic Reviews (PRISMA) checklist was used in selecting the articles, and Joanna Briggs Institute Critical Appraisal was utilized by two independent authors to assess the articles’ quality. A descriptive method was used to analyze the data. Results: The initial review stage found 183 potential articles, but only four satisfied the criteria. The notion of preterm infant cues during breastfeeding is centered on the actions of preterm infants while positioned on their mother's chest. These feeding cues are identifiable before, during, and after breastfeeding and include cues for hunger, self-regulation, stress, satiation, approach, avoidance, and sucking quality. To effectively recognize these cues, tools such as the Preterm Infants Cues Coding System (PFCCS), Infant Driven Scale (IDS), Newborn Individualized Developmental Care and Assessment Program (NIDCAP), and Preterm Breastfeeding Behavior Scale (PIBBS) can be utilized. Conclusion: The study findings highlight the importance of recognizing preterm infant cues during breastfeeding to facilitate proper feeding and developmental care. Observational studies have proven to be an effective means of observing these cues during breastfeeding. By leveraging the cues identified in this review alongside tools such as PFCCS, IDS, NIDCAP, and PIBBS, nurses can accurately interpret preterm infants' breastfeeding cues in neonatal care settings of all levels. This, in turn, can aid in developing care plans that promote better feeding ability outcomes.